Prescribing clarity: mapping the link between antihypertensives and breast cancer - Shadman Newaz; Moontasir Ahmed; Jannat Ara Tina; Talukder Nasif Shahriar; Abdulla Bin Hridoy; Supritom Sarker; Mohammad Zakaria Al-Aziz; Md. Robed Amin (Journal of Current Oncology and Medical Sciences)
Introduction: The relationship between antihypertensive medication and breast cancer outcomes remains a subject of growing interest in clinical research. This systematic review aims to evaluate the potential associations between antihypertensives and breast cancer outcomes, providing a detailed synthesis of current evidence and identifying areas for future research.